New Legal Challenges of Basketball Players Contract Law - Caşın, Mesut Hakkı (Sports and Law: Finding a Balance Between the Game and the Rules, 2026)
This article examines the evolving legal challenges of professional basketball player contracts in the context of globalization, technological transformation, and cross-border employment. Focusing on international player transfers, salary structures, and emerging payment mechanisms such as cryptocurrencies, the study analyses how traditional contractual frameworks are increasingly exposed to legal uncertainty. Particular emphasis is placed on the role of the Basketball Arbitral Tribunal (BAT) as a specialized dispute resolution mechanism applying the ex aequo et bono standard under Swiss arbitration law. By evaluating BAT jurisprudence alongside contemporary developments such as blockchain-based payments and digital market expansion, the article demonstrates how basketball contract law is adapting to new economic and regulatory realities. The study concludes that BAT has developed a coherent and predictable body of principles that strengthens contractual compliance, while technological innovations simultaneously offer efficiency gains and generate new legal risks requiring further regulatory clarification.